Reform of the economic provisions of the constitution: Why national progress is at stake - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2005)
The Philippine Constitution contains many strong restrictions targeted against the flow of foreign capital in specific areas of economic activities. These restrictions were the same ones that were incorporated into the nationalistic provisions of the 1935 Constitution when its framers were anticipating future political independence. This paper discusses the beneficial aspects of lifting or liberalizing these restrictions on foreign capital in the Philippine context. Specifically, the restrictions relate to the prohibition of foreign individuals to engage in land ownership, in the exploitation of natural resources, and the ownership of public utilities. Corporations are allowed to participate in these activities only if they have equity ownership only to the maximum extent of 40 percent. In other words, foreign capital can only be a strict minority participation in corporate enterprises to be allowed in these economic activities. These provisions have hurt Philippine development over the years. Despite the liberalization of many aspects of the economy, including those in the area of trade, industry, and other aspects of the economy, these economic restrictions continue to hold because they are part of the Constitutional document. Some of these provisions of the Constitution could be relaxed through more liberal citizenship rules. But the basis of citizenship - jus sanguinis or blood relations- is also very restrictive. The need to improve the performance of the Philippine economy requires that these restrictions be examined and reformed. A direction of such reforms would be to place them out of the Constitutional framework - as is the case with most modernizing countries - and put them within the realm of ordinary legislation. In this way, they can be debated more openly and the policies could be suited up to changing conditions and the need for change of the economy.
Keywords: 330; Philippine economy; Economics and Law; Constitutions; Economic development; Foreign direct investments; Economic restrictions; Kapitalverkehrspolitik; Protektionismus; Wirtschaftsrecht; Wirkungsanalyse; Direktinvestition; Wirtschaftspolitik; Entwicklung; Philippinen